2010
DOI: 10.3758/app.72.4.1130
|View full text |Cite
|
Sign up to set email alerts
|

Task integration in time production

Abstract: ). Although this is an artificial laboratory task, it is relevant to everyday activities such as that occurring when a speaker who is delivering a talk needs to be sure to end on time. Unlike situations occurring outside the laboratory, however, arbitrary units of time were used in order to examine the effects of secondary-task demands on training and retention of a new skill, not one previously developed for producing known time intervals such as seconds and minutes. Healy et al. (2005) found circumstances un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…However, in previous studies using the time estimation task (e.g., Healy et al, 2005;Wohldmann et al, 2010Wohldmann et al, , 2012, most of the learning occurred in the first block of training trials, so the crucial predicted interaction of secondary-task continuity and phase might only be evident when considering the first block of trials (i.e., a significant three-way interaction of secondary-task continuity, phase, and block might occur). Indeed, as in the earlier studies with this task, we observed a significant interaction of phase and block, reflecting the fact that performance (as measured by proportional absolute error) was much worse in the first block of the first phase than in any other block.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in previous studies using the time estimation task (e.g., Healy et al, 2005;Wohldmann et al, 2010Wohldmann et al, , 2012, most of the learning occurred in the first block of training trials, so the crucial predicted interaction of secondary-task continuity and phase might only be evident when considering the first block of trials (i.e., a significant three-way interaction of secondary-task continuity, phase, and block might occur). Indeed, as in the earlier studies with this task, we observed a significant interaction of phase and block, reflecting the fact that performance (as measured by proportional absolute error) was much worse in the first block of the first phase than in any other block.…”
Section: Resultsmentioning
confidence: 99%
“…Wohldmann et al (2010Wohldmann et al ( , 2012 provided evidence that when the time estimation task is coupled with a secondary alphabet task, which can be viewed as a graduated counting task, subjects use the number of letters recited as a way to keep track of the amount of time that has elapsed, thereby combining the primary time estimation task with the secondary alphabet task into a single functional task. Such a strategy would also be possible for the distance estimation task used here, because the line cue grew at a constant rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, previous research has demonstrated that during duration training procedures, younger adults learn to associate progress on an ongoing task with the trained durations. Once duration-task progress associations are learned, participants often use ongoing task progress to inform later time estimates of the same or similar ongoing tasks (e.g., Wohldmann, Healy, & Bourne, 2010; 2012). Perhaps if older adults were required to process the duration relevant information as part of the ongoing task, they might be more likely to utilize memory for this information to make prospective estimates.…”
Section: Discussionmentioning
confidence: 99%
“…We explained the strong specificity observed in this situation by proposing that subjects integrate the time production task and the alphabet task into a single functional task, rather than treat each task separately (see Hsiao & Reber, 2001;Rah, Reber, & Hsiao, 2000;Schmidtke & Heuer, 1997, for similar theoretical conclusions about dual task processing; but also see Ruthruff, Van Selst, Johnston, & Remington, 2006, for a different conclusion). A subsequent study of ours manipulated in separate experiments either the characteristics of the primary time production task or the characteristics of the secondary alphabet task to provide support for this functional task principle (Wohldmann, Healy, & Bourne, 2010). Experiment 1): Equal pacing.…”
Section: Time Production: Task Integrationmentioning
confidence: 97%